Linear and non-linear compression wave interaction with saturated porous layer - Gubaidulin, Amir A.; Boldyreva, Olga Yu.; Dudko, Dina N. (Vietnam Journal of Mechanics, 2010)
Features of compression waves propagation in a gas-saturated porous medium have been investigated. The passage of wave from gas to porous medium and its reflection from rigid wall has been studied. The mathematical two-velocity model with two stress tensors has been used. Both non-linear and linear approaches have been employed. Features of acoustic wave transmission in a porous layer and following reflection from obstacle have been investigated. The results of the linear analysis allow us to determine the role of non-linear effects in wave propagation and reflection phenomena in saturated porous media and to interpret the results of acoustic wave interaction with porous layer obtained by experiment or finite-difference method